A Cultural History of Youth in the Modern Age - Alexander, Kristine; Sleight, Simon (The Cultural Histories Series, 2022)
A Cultural History of Youth presents historians, scholars and students of related fields with a comprehensive and interdisciplinary overview of youth from ancient times to modernity.